Effective Management by Local Government Administrators Based on the Principles of Good Governance. A Case Study of Talo Maena Subdistrict Administrative Organization, Thung Yang Daeng District, Pattani Province - อาแด นาซีฟะห์; ยีดิง อีกมัล; นิแม นิมูฮำหมัดฮาฟิส; มินทราศักดิ์ นินุสรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this quantitative research were to study the attitudes of 44 personnel within the Talo Maena Subdistrict Administrative Organization (SAO) in Thung Yang Daeng District, Pattani Province—comprising 9 civil servants and 35 staff members—toward the executives’ organizational management based on good governance principles and to propose effective performance guidelines by utilizing descriptive statistics such as frequency distribution, percentages, mean (x̄), and standard deviation (S.D.) presented in tabular format, which ultimately revealed that the personnel’s overall attitude was at a significantly high level across all dimensions, led by Responsiveness (x̄= 4.53), followed by Equity (x̄= 4.47), Accountability (x̄= 4.47), Participation (x̄=4.43), Transparency (x̄= 4.43), Efficiency (x̄= 4.43), Consensus Orientation (x̄= 4.41), Rule of Law (x̄= 4.40), Decentralization (x̄= 4.40) Effectiveness (x̄= 4.37), 2.) leading to the recommendation that the organization must strictly adhere to legal regulations while integrating compassion and respect for local traditions, emphasizing transparency, merit-based recruitment, and inclusive participation of both majority and minority voices, alongside cost-effective budgeting to ensure public trust and maximum benefit.